PROFIL USAHA KERAJINAN SULAMAN NARAS DI DESA NARAS KECAMATAN PARIAMAN UTARA KOTA PARIAMAN PROPINSI SUMATERA BARAT - Wisliana Wisliana; Desti Irja; Aswandi Bahar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims 1) To determine Crafts Embroidery Business Overview Naras Naras in the village of Pariaman. 2) To find Resources in persons Crafts Embroidery Business Naras. 3) To know Productivity Crafts Embroidery Naras. 4) To know Naras Embroidery Craft Marketing Techniques of data collection were interviews, observation, documentation. While the source of the data is that other research informants Business Owners, Craftsmen, Disperindag and village heads. Methods This study was a descriptive study with a qualitative approach. The results of this study are very attractive Embroidery Craft by People of West Sumatra up to foreign countries. Embroidery Craft NARAS has been inherited from ancestors Entrepreneurs Craft 1980 Embroidery Naras This is the original woman who comes from the village of Pariaman District of North Naras Pariaman but craftsmen mostly from Pariaman District of the North but from different villages. Types of Crafts Needlework consists of 1) the bride dress 2) Accessories including the bride bride shoes, 3) weddings Embroidery, 4) Salendang Embroidery, 5) Wear Embroidery, 6) Picture wall, 7) Close the hood of food. Embroidery craft is the raw material consists of satin, velvet, lame cloth, gold thread and yarn manufacturing process uses satin embroidered pemidangan human hand but there is a process of making the bride dress mostly been wear embroidery machine. This effort in promoting the business of crafts embroidery Disperindag also involved in efforts to promote crafts embroidery so that in opening this business offices also assist in the process of initial funding.Key words: Profiles, Business, Craft, Embroidery Naras